Readiness of Hospitality Management Students on their On-the-job Training - Joseph Famin; Maria Fe Factao; Martin Napalinga; Debbie Manalo; Ma. Ciaina Araneta; Marry Claire Faro (IC-ITECHS, 2022)
On-the-job training is one of the requirements for graduating students. This guides the students to identify their knowledge, competence, and readiness towards having their chosen field and specialization. The purpose of this study is to identify the level of readiness of fourth-year (4th) BS Hospitality Management students of Iloilo Science and Technology University—Miagao Campus during the first semester of the academic year 2021–2022. The study employed a descriptive survey method. Findings revealed that when taken as a whole, the respondents were partially ready for their internship. When classified, the findings revealed that there is no significant difference in the level of readiness of fourth (4th) Year BS Hospitality Management students as to class section and family monthly income, but a significant difference when it comes to sex and academic performance. Class section and family monthly income cannot affect their readiness for on-the-job training. Students can still be ready for his/her internship regardless of what group he/she belong to, and since the respondents are beneficiaries of a "Free Tuition Program," they can use this as one of the means to sustain their needs aside from working. Thus, for these variables, the null hypothesis of this study is accepted. On the other hand, the results show that sex and academic performance affect students’ readiness on their on-the-job training. Sexuality in the hospitality workplace seeks specific activities and/or roles to be performed, especially when it comes to hard skills in kitchen and dining, and soft skills for personal and actual front services. While on academic performance, most of the attentive and top students are worrier and are concerned with their internship grades as this is one of the basis to define their academic ranking. This will be their motivation to be ready and perform well during their internship, as it is one of the major criteria next to research study. While good and fair- rated students are being contented with their neutral and tolerable academic performance as long as they can pass and finish their degree. The level of their readiness depends on their academic goals and/or purpose. With this, for the variables sex and academic performance, the null hypothesis for this study is rejected. As suggested, the students must develop more skills towards different competencies as part of the curriculum. They need it to also excel in different parts of life as a student and as an individual. They should understand that handling academic performance together with real world skills is best for them as they can put theories into realities someday if they will be working with their respective fields. They can have these through enrolling in short courses and skills trainings from various organizations or institutions.